Experimental Study on the Seismic Response of Longhouses Using Scale Models. Issue 1 (2nd January 2020) - Hashim, Huzaifa; Ibrahim, Zainah; Azim Shukri, Ahmad; Hastamam, Siti Nurhanis Yasmin; Lai, Sai Hin
Abstract: Longhouses have a unique architectural value and represent the cultural heritage of ancient human settlements on the highland plateau in various parts of Sarawak, on the island of Borneo. However, seismic events in the locality and in neighbouring countries have increased awareness of and concern over the safety of buildings in the region. These buildings include the longhouse structures, some of which have stood for nearly 50 years and would probably stand for much longer were proper care taken of them. This study presents the use of scale models to initiate investigation on the seismic response of the longhouses. A shaking table was used to simulate the seismic motions. From the experimental work, it was determined that the stilt-like column sections and the roof level of the longhouses have a high risk of excessive deformation during seismic motions.